2020
DOI: 10.1037/dhe0000107
|View full text |Cite
|
Sign up to set email alerts
|

Microaggressions in the learning environment: A systematic review.

Abstract: Microaggressions entail everyday brief, low-intensity events that convey negative messages toward marginalized groups. A systematic review of the literature on microaggressions in the learning environment of higher education was performed from 1998 to 2018 using a modified PRISMA outline. Forty articles on racial microaggressions were categorized as microaggression experiences of all races/ethnicity (27.5%), microaggression experiences of minorities (22.5%), difficult racial dialogues (10%), coping strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 73 publications
1
74
0
2
Order By: Relevance
“…College students of color have long deemed teaching practices culturally unresponsive and have noted how curricula routinely failed to include their cultural histories, identities, and interests. Many of these students have also specified the racial microaggressions and other racist experiences they have had inside and outside of college classrooms (Harper 2015;Harper and Davis 2016;Ogunyemi et al 2020;Suárez-Orozco et al 2019;Yeo et al 2019;Yosso et al 2009). Most black students are taught by white instructors, as ratios of black students to black faculty are often incredibly imbalanced at predominantly white institutions (Harper and Simmons 2019).…”
Section: Upskilling Faculty Members In Teaching Students Of Color Onlinementioning
confidence: 99%
“…College students of color have long deemed teaching practices culturally unresponsive and have noted how curricula routinely failed to include their cultural histories, identities, and interests. Many of these students have also specified the racial microaggressions and other racist experiences they have had inside and outside of college classrooms (Harper 2015;Harper and Davis 2016;Ogunyemi et al 2020;Suárez-Orozco et al 2019;Yeo et al 2019;Yosso et al 2009). Most black students are taught by white instructors, as ratios of black students to black faculty are often incredibly imbalanced at predominantly white institutions (Harper and Simmons 2019).…”
Section: Upskilling Faculty Members In Teaching Students Of Color Onlinementioning
confidence: 99%
“…2,27,28 Although we did not ask respondents to detail these reported instances of discrimination, prior research revealed that physicians from racial minorities frequently described encountering microaggressions in the workplace. [29][30][31] Microaggressions are defined as brief, commonplace, daily, verbal, nonverbal, environmental slights, insults, invalidations, and indignities -intentional or unintentional -directed toward a marginalized group. 32 There is literature that details the detrimental mental health effects of microaggressions.…”
Section: Discussionmentioning
confidence: 99%
“…32 There is literature that details the detrimental mental health effects of microaggressions. 31,33 use to respond to instances of racial discrimination in the workplace. 34 Other suggested actions to mitigate discriminatory behavior and promote diversity include the identification of best practice efforts to recruit and retain faculty from minority groups, addressing obstacles to advancement, and implementing strategies to promote members of minority groups to positions of leadership.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations